LATE EVALUATION OF PATIENTS OPERATED FOR GASTROESOPHAGEAL REFLUX DISEASE BY NISSEN FUNDOPLICATION - RIBEIRO,Maxwel Capsy Boga (2016)
ABSTRACT Background: Surgical treatment of GERD by Nissen fundoplication is effective and safe, providing good results in the control of the disease. However, some authors have questioned the efficacy of this procedure and few studies on the long-term outcomes are available in the literature, especially in Brazil. Aim: To evaluate patients operated for gastro-esophageal reflux disease, for at least 10 years, by Nissen fundoplication. Methods: Thirty-two patients were interviewed and underwent upper digestive endoscopy, esophageal manometry, 24 h pH monitoring and barium esophagogram, before and after Nissen fundoplication. Results: Most patients were asymptomatic, satisfied with the result of surgery (87.5%) 10 years after operation, due to better symptom control compared with preoperative and, would do it again (84.38%). However, 62.5% were in use of some type of anti-reflux drugs. The manometry revealed lower esophageal sphincter with a mean pressure of 11.7 cm H2O and an average length of 2.85 cm. The average DeMeester index in pH monitoring was 11.47. The endoscopy revealed that most patients had a normal result (58.06%) or mild esophagitis (35.48%). Barium swallow revealed mild esophageal dilatation in 25,80% and hiatal hernia in 12.9% of cases. Conclusion: After at least a decade, most patients were satisfied with the operation, asymptomatic or had milder symptoms of GERD, being better and with easier control, compared to the preoperative period. Nevertheless, a considerable percentage still employed anti-reflux medications.